Study of fatigue life of glass fibre/zirconia hybrid composites using an ultrasonic technique - Srivastava V.K.; Prakash R. (My University, 2025)
The use of hybrid composite materials with confidence in aerospace structures is possible only when suitable non-destructive testing techniques are developed. In this study, an ultrasonic technique has been used to evaluate the fatigue life of a glass fibre/zirconia hybrid composite to which zirconia particulate filler had been added to increase the absorbing capacity during fracture of the glass fibre-reinforced plastic. The results indicate that the fatigue life of the hybrid composite decreases with increasing ultrasonic attenuation. The failure mode of the hybrid composite was studied by scanning electron microscopy, which revealed that the maximum stress is concentrated around the fibres. © 1987.